Ethnic Quotas, Political Representation and Equity in Asia Pacific. Issue 3 (3rd July 2022) - Tan, Netina; Preece, Cassandra
ABSTRACT: Do quotas raise legislative diversity and reduce inequities between the dominant and minority groups? This paper studies how quota mechanisms affect legislative diversity in 11 countries in Asia Pacific and ethnic equity between groups in three cases. We find that quota mechanisms have improved legislative diversity. However, the socio-economic status of targeted minority groups continues to lag behind the dominant group in each case presented. Our findings highlight the limitations of institutionalist solutions to address deeper structural inequities between ethnic groups.